Multilingual Skills provide Export Benefits and Better Access to New Emerging Markets - Bel Habib, Ingela (Sens public)

(untitled) (Département des littératures de langue française, 2011)
The author analyses in a study the effects of linguistic skills on the export performance of German, French and Swedish SMEs. Contrary to popular belief, English does not suffice in